Motivation and Teaching-learning Process - Saini, Sarita (JOURNAL OF INDIAN EDUCATION, 2011)
Presently, it is frequently heard that students are under stress and demoralised, because of one reason or another. Some of the students even do not feel like to attend the school. The author has the opinion that the major key factor of distress among today’s youth is lack of proper motivation and positive feedback from teachers as well as parents. This write-up focus on the role of motivation during teaching-learning process in school, and role of parents in motivating their children at home. In this article an attempt has been made to suggest some very useful and practical strategies to motivate the students. It will not only make the teaching interesting but also improve the achievement of students.